(untitled) (Latakia University Journal -Biological Sciences Series, 2022)
The life tables parameters of larval ectoparasitoid Bracon concolorans (Marshall,1900) was studied on mature larvae of tomato leafminer Tuta absoluta (Meyrick) (Lepidoptera: Gelechiidae) in laboratory of insects at Latakia Agriculture Research Centre,Latakia,Syria ,during2019-2020, at 25-28°C and 60±10% R.H with sexual reproduction and arrhenotokous parthenogenesis The parameters were calculated using Two Sex-MSChart. Results showed that the following values (sexually reproduction): net reproductive rate R0= 46.58±7.2 Female/female/generation, the intrinsic rate of increase (r)= 0.2187±0.0102 Female/female/day, mean generation time (T)= 17.559±0.302 days, The doubling time of population (DT)= 3.1684 days, gross reproductive rate (GRR)= 50.91±7.656 individuals/offspring, Finite rate of increase (λ)= 1.2445±0.0127, fecundity (F) =89.58±6.719 eggs/female, total developmental times of immature mean= 9.22±0.13 days, Adult pre-oviposition period of female adult (APOP)= 2.96±0.07, Mean length Adult female age = 36.08±1.93 days. The Mean age of the adult male is 34.78±0.4 days .In (arrhenotokous Parathenogenesis):, Finite rate of increase (λ)= 1, net reproductive rate R0, the intrinsic rate of increase (r) and gross reproductive rate (GRR) =0. Values of The life tables parameters in this study indicate to importance of parasitoid B. concolorans to use it in integrated management programs of tomato leafminer T. absolute in the regions of its distribution.